Nonpharmacologic Interventions for the Self-Management of Anxiety in Parkinson’s Disease: A Comprehensive Review - Susan K. Chandler; Jo Lynne Robins; Patricia A. Kinser (Behavioural Neurology)
Anxiety in Parkinson’s disease (aPD) is underdiagnosed, undertreated, and understudied. As many as 50% of persons diagnosed with Parkinson’s disease (PD) are reported to suffer from anxiety. Current treatment is largely pharmacologic, which can result in a myriad of undesirable and unsafe side effects. The aim of this paper is to examine intervention studies of self-managed nonpharmacological strategies for the treatment of anxiety. A comprehensive review was conducted on experimental or quasi-experimental trials that included self-management approaches for the nonpharmacologic treatment of anxiety as a primary or secondary aim or outcome measure. Thirteen studies were identified from four databases. Study quality demonstrated variability in design and delivery of self-managed interventions; sample sizes were small; anxiety was most commonly a secondary aim; and the use of anxiety measures varied widely. Statistical significance was evident in slightly more than 50% of the anxiety intervention studies. A common element in the interventions in all studies was the focused use of breath. Further research is needed to determine the feasibility of using focused breathing, alone, as an intervention for the self-management of anxiety in Parkinson’s disease.